Social innovation and networks: linkages and challenges - Ferreiro, M. F.; Sousa, C. (Proceedings of the 12th European Conference on Innovation and Entrepreneurship, 2017)
The concept of social innovation is not new but “has returned to prominence in the last 15 years, after a period of neglect” (McCallum, Moulaert et al, 2009, p.2). However, and according to Ionescu, “social innovation is a relatively new analysis subject when it comes to the development of the theoretical approaches which rend the projected social development possible and efficient, but also within the context of other approaches which put emphasis on dispersed knowledge, decentralization and the capacity of communities and social groups to self-organize and formulate specific and new solutions to the problems they are dealing with” (Ionescu, 2015, p.54). The history of the concept revels that the association between the terms ‘innovation’ and ‘social’ has moved from its consideration as one of the dimensions of political and organizational change (Benjamin Franklin, Emile Durkheim, Joseph Schumpeter) to a change in itself: “the introduction of the social to innovation - as well as of the innovation to the social” (McCallum, Moulaert et al, 2009, p. 2). According to the same authors, “The concept enlarges the economic and technological reading of the role of innovation in development to encompass a more comprehensive societal transformation of human relations and practices (Moulaert and Nussbaumer 2008, in McCallum, Moulaert et al, 2009, p.2), being much more than innovations that enhance economic efficiency (Moulaert et al. 2005, 1973; Moulaert and Nussbaumer 2005, in McCallum, Moulaert et al, 2009, p.2) The work of Chambon, David and Devevey (1982) (Que sais- je?) offers an important synthesis on social innovation, namely the “relationship between social innovation and the pressures bound up within societal changes, and show how the mechanisms of crisis and recovery both provoke and accelerate social innovation”. According to the authors, “social innovation signifies satisfaction of specific needs thanks to collective initiative, which is not synonymous with state intervention” (in Moulaert, 2009, p.13), and “can occur in different communities and at various spatial scales, but is conditional on processes of consciousness raising, mobilization and learning” (Idem, ibidem, p.13). The literature on the subject refers also the different elements involved in the dynamic of social innovation: objectives, processes, results and impact. In fact, “social innovations are innovations in both their ends and their means” (Ionescu, 2015, p.56); “social innovation is innovation in social relations, as well as in meeting human needs” (McCallum, Moulaert et al, 2009, p.2).